A further editorial guideline for writing manuscript in the field of social science A special perspective for African journal of business management - Alam, Gazi Mahabubul (Academic Journals, 2011)
With the breathtaking success of African Journal of Business Management-AJBM in the recent years, has become one of most commanding podiums for the scholar especially from the developing world. In 2009, not only its impact factor has increased substantially, but also one of its published papers “has been selected by Essential Science IndicatorsSM from Thomson Reuters as the most-cited paper in the research area of Economics and Business”. With its success, submissions have increased dramatically with an equal increased figure of rejection. Huge rejection is not good news for any party. It is now thus important to provide a better editorial guideline for research community to prepare their works making it more suitable and also to help them in targeting the right journal for appropriate readership and audience. This editorial is prepared with the consultation of more than 800 papers submitted from around the globe for the publication in AJBM. A portion of them are published, while a significant numbers are also rejected. Since, research community from Africa, Fareast, Middle-East and the Western world are contributing for AJBM. Every community has some strengths and weaknesses to offer lessons for others. Keeping this in mind, it is thus also important to have a common understanding about the research in business management and writing manuscripts. With an optimistic attitude, this editorial aims to provide a guideline for writing manuscript in the field of Social Science with a special focus on AJBM.